Evaluation of the impact of dental prophylaxis on the oral microbiota of dogs. - Rebecca Flancman; Ameet Singh; J Scott Weese (PLoS ONE)
Periodontal disease is one of the most commonly diagnosed oral diseases in dogs and can result from undisturbed dental plaque. Dental prophylaxis is a routinely practiced veterinary procedure, but its effects on both the plaque and oral microbiota is not fully understood. The objectives of this study were to evaluate the impact of dental prophylaxis on the composition of the supragingival plaque and composite oral microbiota in clinically healthy dogs and to determine if composite sampling could be used in lieu of sampling the plaque microbiota directly. Thirty dogs received a dental prophylaxis. Supragingival plaque and composite oral samples were collected just prior to, and one week after dental prophylaxis. A subsample of 10 dogs was followed, and additional samples were collected two and five weeks post-prophylaxis. The V4 region of the 16S rRNA gene was used for Illumina MiSeq next-generation sequencing. Results demonstrate that decreases in Treponema as well as increases in Moraxella and Neisseria distinguished the plaque pre- and one week post-prophylaxis timepoints (all P<0.05). Within the oral microbiota, the initially dominant Psychrobacter (20% relative abundance) disappeared one week later (P<0.0001), and Pseudomonas became the dominant taxon one week after treatment (80% relative abundance, P<0.0001). A rapid transition back towards the pre-dental prophylaxis microbiota by five weeks post-treatment was seen for both niches, suggesting the canine oral microbiota is resilient. Direct comparison of the two environments yielded striking differences, with complete separation of groups. Firmicutes (40%) and Spirochaetes (22%) predominated in the plaque while Proteobacteria (58%) was predominant in the oral microbiota. Greater richness was also seen in the plaque microbiota. This study reveals that prophylaxis had a profound impact on both the plaque and oral microbiota, and the longitudinal results help elucidate the pathophysiology of periodontal disease. The results suggest that oral swabs are a poor proxy for plaque samples and highlight the need to study specific oral niches.